PROTOTYPE PENGERING BAHAN BAKU DAN PRODUK BIOPELET DITINJAU DARI ENERGI H2O YANG TERUAPKAN KE UDARA - Lestari, Sutini Pujiastuti; Aswan, Arizal; Sumarna, Herlin (KINETIKA, 2019)
Energy consumption in Indonesia is still dominated by the use of fossil-based energy, especially petroleum and coal. Therefore, biomass as a renewable energy source is an effort to reduce the use of fossil energy in Indonesia. Biopellet is one of the processing of biomass into solid fuel. In the process stage of making biopellet used dryer. In the prototype of drying machine, the independent variables are variation of raw material mix and fixed variable such as air velocity, drying time, and drying temperature. Based on the results of the research, the H2O concentration was evaporated and the H2O heat in the air was highest in the 60% mixture of wood powder: 40% rice husk. From mass of H2O evaporated equal to 14.84 gr and H2O heat in air equal to 136.506 grcal analyzed moisture content and calorific value of biopelet product. Water content obtained at 6.716% and the calorific value of 5,188.8506 grcal/gr has met the SNI 8021-2014 standard.